Food-Sharing Practices Online in the Facebook Group Cambridge Bay News - Dunn, Laura; Gross, Pamela (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2016)
Cambridge Bay News is a popular Facebook group that residents of Iqaluktuuttiaq use to communicate within the town. Many members also use the group to share country food with others. Our paper looks at residents’ practices of sharing food on Cambridge Bay News and the impact these practices have on relationships within the community. Comparing these practices with oral history and anthropological accounts of Inuinnait sharing practices, we examine how food sharing is changing relationships within Iqaluktuuttiaq and between people and the land in response to ongoing colonial practices.